Taxation and development : lessons from Colombian experience - Bird, R.M.; Lancaster, Carol; Van de Walle, Nicolas (massachusetts : Harvard University Press, 1970)
The study is organized in six chapters. The first two provide the descriptive and analytical setting for the more detailed tax analysis of the next three, and the last chapter sketches some broader considerations affecting tax reform in Colombia
Includes index
sju 22/01/2019
Loans
Keywords: Economic development; Institution building; Democratization; Developing countries